Buprenorphine reverses neurocognitive impairment in EcoHIV infected mice: A potential therapy for HIV-NCI - Murphy, Aniella J.; Kelschenbach, Jennifer; He, Hongxia; Chao, Wei; Kim, Boe-Hyun; Volsky, David J.; Berman, Joan W. (Frontiers in Immunology, 2022)
Thirty-eight million people worldwide are living with HIV, PWH, a major public health problem. Antiretroviral therapy (ART) revolutionized HIV treatment and significantly increased the lifespan of PWH. However, approximately 15-50% of PWH develop HIV associated neurocognitive disorders (HIV-NCI), a spectrum of cognitive deficits, that negatively impact quality of life. Many PWH also have opioid use disorder (OUD), and studies in animal models of HIV infection as well as in PWH suggest that OUD can contribute to HIV-NCI. The synthetic opioid agonist, buprenorphine, treats OUD but its effects on HIV-NCI are unclear. We reported that human mature inflammatory monocytes express the opioid receptors MOR and KOR, and that buprenorphine reduces important steps in monocyte transmigration. Monocytes also serve as HIV reservoirs despite effective ART, enter the brain, and contribute to HIV brain disease. Using EcoHIV infected mice, an established model of HIV infection and HIV-NCI, we previously showed that pretreatment of mice prior to EcoHIV infection reduces mouse monocyte entry into the brain and prevents NCI. Here we show that buprenorphine treatment of EcoHIV infected mice with already established chronic NCI completely reverses the disease. Disease reversal was associated with a significant reduction in brain inflammatory monocytes and reversal of dendritic injury in the cortex and hippocampus. These results suggest that HIV-NCI persistence may require a continuing influx of inflammatory monocytes into the brain. Thus, we recommend buprenorphine as a potential therapy for mitigation of HIV brain disease in PWH with or without OUD.